4-Acetoxydolastane Diterpene from the Brazilian Brown Alga Canistrocarpus cervicornis as Antileishmanial Agent - Elizandra Aparecida Britta; Celso Vataru Nakamura; Everson Miguel Bianco; Adriana Oliveira dos Santos; Renato Crespo Pereira; Tania Ueda-Nakamura; Benedito Prado Dias Filho (Marine Drugs, 2011)
Natural marine products have shown an interesting array of diverse and novel chemical structures with potent biological activities. Our study reports the antiproliferative assays of crude extracts, fraction and pure compound (4R,9S,14S)-4α-acetoxy-9β,14α-dihydroxydolast-1(15),7-diene (1) obtained from brown alga Canistrocarpus cervicornis showing the antileishmanial activity. We showed that 1 had a dose-dependent activity during 72 h of treatment, exhibiting IC50 of 2.0 µg/mL, 12.0 µg/mL, and 4.0 µg/mL for promastigote, axenic amastigote and intracellular amastigote forms of Leishmania amazonensis, respectively. A cytotoxicity assay showed that the action of the isolated compound 1 was 93.0 times less toxic to the macrophage than to the protozoan. Additionally, compound 1 induced ultrastructural changes, including extensive mitochondrial damage; decrease in Rh123 fluorescence, suggesting interference with the mitochondrial membrane potential; and lipid peroxidation in parasite cells. The use of 1 from C. cervicornis against L. amazonensis parasites might be of great interest as a future alternative to the development of new antileishmanial drugs.